Smart niosomes of temozolomide for enhancement of brain targeting. (10th October 2018) - De, Anindita; Venkatesh, Nagasamy; Senthil, M; Sanapalli, Bharat Kumar Reddy; Shanmugham, R; Karri, Veera Venkata Satyanarayana Reddy
Drug delivery to the brain is challenging because of the low permeability of blood–brain barrier, and therefore, optimum concentration of chemotherapeutics in the target area specifically for glioblastoma, an aggressive brain tumor, opens a new path of research. To achieve the goal, the oral alkylating agent temozolomide was incorporated into niosomes, and the surface was modified with chlorotoxin, a small 36 amino acid peptide discovered from the venom of scorpion Leiurus quinquestriatus . Active targeting using nanosized particles facilitates an increase in the accumulation of drugs in the cerebri by 3.04-folds. Temozolomide-loaded niosomes were prepared using conventional thin-film hydration method and characterized. Niosomes coated with chlorotoxin were produced with the size of 220 ± 1.45 nm with an entrapment efficiency of 79.09 ± 1.56%. Quantitative tissue distribution studies indicate enhanced permeation of the drug into the brain because of surface modification with less deposition in the highly perfused organs.